Sexting, intimate and sexual media practices and social justice - Dobson, Amy (Springer, 2018)
Dobson argues for an orientation of research into intimate and sexual media practices around power and social justice. She frames intimate and sexual media practices in terms of their potential social and economic value, rather than in terms of risks and pathologies. Dobson, however, points to the limits of understanding sexting and other kinds of intimate media practices as ‘agentic media production’, through a careful consideration of research into girls’ and young women’s digital media cultures. To understand self and media production as an individual act is to ignore the ways in which it is socially and technically conditioned, she argues. A social justice orientation becomes imperative in a techno-social context where personal relations have been rapidly monetised through digital media platforms in ways that work to propose a new version of ‘the social’ centred around quantified hierarchies of visibility and status.